Cytobrush cytology patterns of early postpartum dairy cows. (August 2020) - Kusaka, Hiromi; Hasegawa, Ryo; Nishimoto, Namiko; Kawahata, Masatoshi; Bandai, Kazuhiro; Miura, Hiroshi; Kikuchi, Motohiro; Sakaguchi, Minoru
Highlights: Cytological endometritis (CE) causes subfertility in lactating dairy cows. Cytobrush cytology (CC) has been recommended for diagnosing CE. A sequential description of CC during the early postpartum period is needed. Early (3 weeks) postpartum smear clarity was reduced, affecting the accuracy of CC. Counting 300 cells is recommended for diagnosing CE at 3–7 weeks postpartum. Abstract: Endometrial cytobrush cytology has been recommended as a reliable method for determining the percentage of polymorphonuclear leukocytes (PMN%) in cattle smears to diagnose cytological endometritis (CE). In this study, the clarity of cytobrush　cytological smears and the influence of different sample evaluation methods (number　and types of cells counted) on CE diagnosis were evaluated. Samples from 28 lactating　Holstein cows were collected weekly between 3 and 7 weeks postpartum. Smear clarity, 　based on cell density, quality of cell morphology, and red blood cell contamination, 　was significantly poorer at 3 weeks than between 5 and 7 weeks postpartum. Five　different cell counting methods (C100, C200, C300, C400, and C500) were used, 　where 100–500 nucleated cells (endometrial epithelial cells, PMN consisting of neutrophils, eosinophils and basophils, lymphocytes, and macrophages) were counted. Agreement of diagnostic results for CE between C300 and C500 and between C400 and C500 was excellent at all observation times. In calculations of the PMN% based on whether the number of lymphocytes and macrophages were or were not excluded in the denominator, exclusion of these cells in the calculations did not affect the diagnosis of CE. While reduced clarity in earlier stage samples might interfere with the accuracy of cytobrush cytology, C300 can be recommended to determine the endometrial PMN%.